2003
DOI: 10.1007/bf02707350
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic properties of Co1+ySnyFe2-2y-xCrxO4 ferrite system

Abstract: The samples of the series Co 1+y Sn y Fe 2-2y-x Cr x O 4 ferrites with x = 0⋅ ⋅0, 0⋅ ⋅1, 0⋅ ⋅2, 0⋅ ⋅3, 0⋅ ⋅4, 0⋅ ⋅5 and y = 0⋅ ⋅05, were prepared by the usual double sintering ceramic technique. The single-phase spinel structure of the samples was confirmed by using X-ray diffractometry technique. The lattice parameter 'a' with an accuracy of ± ± 0⋅ ⋅002 Å were determined using Bragg peaks of XRD pattern. The lattice parameter 'a' decreases with concentration, x, which is due to the difference in the ionic rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…A similar type of behavior for Cr 3+ substituted ferrite system is reported in literature. 18,19 The average particle size was determined from the measured width of diffraction pattern using Scherrer formula…”
Section: Resultsmentioning
confidence: 99%
“…A similar type of behavior for Cr 3+ substituted ferrite system is reported in literature. 18,19 The average particle size was determined from the measured width of diffraction pattern using Scherrer formula…”
Section: Resultsmentioning
confidence: 99%
“…It is evident from Table 1 that, the increase in Ni content causes a lowering in grain size. Pandit et al [18] concluded that the replacement of Fe with Cr +3 in Co-Sn ferrite leads to a decrease in cation vacancies and in turn to a decrease of grain size.…”
Section: X-ray Diffractionmentioning
confidence: 98%
“…The crystallite size of the nanocrystalline samples were calculated using the Debye-Scherrer formula given in Eq. (1).…”
Section: Xrd Analysismentioning
confidence: 95%
“…[1]. Among the soft ferrites, Ni-Zn ferrites are of commercial importance due to their high frequency applications in different devices such as radio frequency coils, transformer cores, etc.…”
Section: Introductionmentioning
confidence: 99%